IMPACT OF SEXUAL HARASSMENT ON CHILDREN’S WELFRAE IN BUSIU SUB-COUNTY, MBALE DISTRICT. - MUZAKI ESTHER (My University, 2024)
ABSTRACT Despite of government interventions through policy and legislation, children‘s welfare is still low. Children re known of school dropout, lack of decent shelter and are affected and infected by diseases such as HIV/AIDS. The main objective of this study will be to assess the impact of sexual harassment on children‘s welfare in Busiu Sub County in Mbale district. Specifically, the study was guided by the following objectives namely, to identify the factors contributing to sexual harassment of children in Busiu Sub county in Mbale district, to examine the impact of sexual harassment on children‘s welfare in Busiu Sub county in Mbale district and to assess strategies for preventing sexual harassment and improve children‘s welfare in Busiu Sub county in Mbale district. Data was collected from 80 respondents in Busiu Sub County who included opinion leaders, child welfare officers and parents. Data was collected using surveys and interviews. Study participants were identified using probability and non-probability sampling. The study employed a mixed research approach using descriptive study and case study designs and data processing was done through editing of the data which will be coded for further data analysis. Data from questionnaires was analyzed using both descriptive statistics while interview data was analyzed using frequency analysis by counting the number of times of responses had by the respondents. Findings showed that stressful home environment contributed sexual harassment. Other factors contributing to sexual harassment are lack of self-esteem, poor communication, misunderstanding boundaries and tension among family members. Findings further revealed that sexual harassment Increases risks and psychological difficulties, depression and anxiety disorders. Behavioral problems such as substance abuse and antisocial behavior among children may also be caused by sexual harassment. Other effect of sexual harassment on children welfare found by the study included increased risk of disease infection like HIV/AIDS and school dropout of children. Further, the study found that improving communication, teaching children the importance of body privacy and about boundaries may help to curb sexual harassment. Other measures of curbing sexual harassment revealed by the study are improving policy and legislation to protect children‘s right as well as teaching children appropriate boundaries and privacy. The study recommended undertaking community mobilization and awareness creation on the dangers of sexual harassment and to increase community vigilance against the vice as well as increasing budgetary funding for child protection and welfare services.